Effect of Creosote and Copper-Chrome-Arsenic (CCA) Treatments on the Compressive Strength of Haldu Wood (Adina cordifolia Benth & Hook) - Edwin, Leela; Thomas, Saly N. (Fishery Technology, 2025)
The effect of preservative treatment on a secondary species of wood, Adina cordifolia (Haldu) was studied. Panels were impregnated with creosote, an oil borne preservative, and copper-chrome- arsenic (CCA), a water borne preservative, through immersion treatment. The compressive stress parallel to grain of panels at various preservative retention levels was assessed to find out the change in mechanical strength. An average reduction of 14% compressive stress was noticed in CCA treated haldu panels and slight increase of 2 - 6% was observed in creosote treated panels.